Role of CD1d and iNKT cells in regulating intestinal inflammation - Lee, Sung Won; Park, Hyun Jung; Van Kaer, Luc; Hong, Seokmann (Frontiers in Immunology, 2024)
Invariant natural killer T (iNKT) cells, a subset of unconventional T cells that recognize glycolipid antigens in a CD1d-dependent manner, are crucial in regulating diverse immune responses such as autoimmunity. By engaging with CD1d-expressing non-immune cells (such as intestinal epithelial cells and enterochromaffin cells) and immune cells (such as type 3 innate lymphoid cells, B cells, monocytes and macrophages), iNKT cells contribute to the maintenance of immune homeostasis in the intestine. In this review, we discuss the impact of iNKT cells and CD1d in the regulation of intestinal inflammation, examining both cellular and molecular factors with the potential to influence the functions of iNKT cells in inflammatory bowel diseases such as Crohn's disease and ulcerative colitis.